2023
DOI: 10.1002/alz.13104
|View full text |Cite
|
Sign up to set email alerts
|

Global rural health disparities in Alzheimer's disease and related dementias: State of the science

Lisa Ann Kirk Wiese,
Allison Gibson,
Marc Aaron Guest
et al.

Abstract: INTRODUCTIONIndividuals living in rural communities are at heightened risk for Alzheimer's disease and related dementias (ADRD), which parallels other persistent place‐based health disparities. Identifying multiple potentially modifiable risk factors specific to rural areas that contribute to ADRD is an essential first step in understanding the complex interplay between various barriers and facilitators.METHODSAn interdisciplinary, international group of ADRD researchers convened to address the overarching que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 254 publications
(382 reference statements)
0
6
0
Order By: Relevance
“… 64 , 65 Vascular dementia, the second most diagnosed subtype (up to 20% of cases), often coexists with and is incorrectly diagnosed as Alzheimer’s disease. 66 , 67 The remaining dementias are typically categorized as Lewy body, frontotemporal, or alcohol-related. 68 …”
Section: Results Of the Reviewed Studiesmentioning
confidence: 99%
“… 64 , 65 Vascular dementia, the second most diagnosed subtype (up to 20% of cases), often coexists with and is incorrectly diagnosed as Alzheimer’s disease. 66 , 67 The remaining dementias are typically categorized as Lewy body, frontotemporal, or alcohol-related. 68 …”
Section: Results Of the Reviewed Studiesmentioning
confidence: 99%
“…The major strengths of our large-scale study include the community-based study design that engaged rural-dwelling older adults in China who had received no or very limited school education, a sociodemographic group that has been underrepresented in research on dementia and brain aging 46 and the objective assessment of sleep duration. In addition, using multimodal biomarkers for different brain pathologies assessed with the state-of-the-art techniques (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our large‐scale population‐based study engaged rural‐dwelling older adults in China in a low socioeconomic position who received no or very limited formal education, a sociodemographic group that has been substantially underrepresented in epidemiological and clinical research on dementia and AD. 13 Furthermore, the integration of comprehensive epidemiological, clinical, and cognitive data with AD‐related plasma biomarkers in a subsample allows us to explore the potential neuropathological mechanisms linking multimorbidity load and clusters with cognitive phenotypes. However, our study also has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant given that epidemiological features (eg, prevalence, distribution, and risk factors) of chronic conditions and dementia disorders differ considerably between high-income and low-and middle-income countries as well as between urban and rural populations. [10][11][12][13] Some chronic conditions tend to occur together in older adults due to shared risk factors or common pathophysiological mechanisms, 14,15 so it is important to define different clusters of multimorbidity when investigating multimorbidity. 16 Indeed, previous studies showed that the associations of multimorbidity with dementia varied by different patterns of multimorbidity, 4 suggesting the importance of assessing specific disease clusters when studying the relationship of multimorbidity with cognitive phenotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation